Unusual layer-by-layer growth of epitaxial oxide islands during Cu oxidation - Meng Li (Nature Portfolio, 2021)
Understanding metal oxide growth mechanisms is essential for the precise design and fabrication of nanostructured oxides. Here, the authors use correlated in situ ETEM, data analysis, and DFT to show an unusual layer-by-layer adatom growth mechanism of 3D epitaxial Cu2O nano-islands, regardless of substrate orientation.